Prevalence of Food Allergy in Children: A Cross Sectional Study - Khayriyah Albahi; Esra Oun (AlQalam Journal of Medical and Applied Sciences, 2022)
Aims. The aim of this study was to identify the most common food allergens among children in the Al Ajeilat city, Libya. Methods. A prospective three centers cross-sectional study was conducted on 230 Libyan children with food allergy diagnosed by a doctor, and their ages ranged from 4 months to 14 years. Results. The results showed that the most common food allergens were fruits, with a percentage of 33%, followed by eggs and cow’s milk at 13.9%, then wheat soybeans fish nuts tomatoes at 12%, 7.8%, 6.9%, 6%. Conclusion. Our results showed that fruits, cow’s milk, and egg were most common food allergens in children in the Al-Ajeilat city, Libya. Most of the patients were found to be poly-sensitized. Food allergy remains an important health concern due to increasing prevalence worldwide. Cite this article: Albahi K, Oun E. Prevalence of Food Allergy in Children: A Cross Sectional Study. Alq J Med App Sci. 2022;5(2):592-595. https://doi.org/10.5281/zenodo.7452246